Improving Quality Assurance in European Vocational Education and Training Factors Influencing the Use of Quality Assurance Findings - Visscher, Adrie J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2009)
Many resources are invested in the development and introduction of Quality Assurance Systems in educational institutions all over the world. Our assumption is that, as a result of quality assurance activities, practitioners obtain information about their own functioning and institutional performance which is new and valuable to them and which therefore will form a basis for them to improve performance. This assumption proves to be naïve; too often performance feedback is under-utilized, and evaluations become void, legitimizing rites instead of a basis for organizational learning and the improvement of institutions. The aim of this book was to find out when educational institutions do transform Quality Assurance data into actions to improve performance, and how the use of such data can be promoted. This volume reports on the study of Quality Assurance structures and activities in 36 educational institutes in 6 European Countries and presents guidelines for Quality Assurance.
to the Problem of the Under-Utilisation of Quality Assurance Data, and the Research Approach -- A Theoretical Framework for Analysing the Implementation and Effects of Quality Assurance Systems in European VET -- Factors Influencing the Use of Quality Assurance Data in Dutch (I)VET for the Health Care Sector -- Factors Influencing the Use of Quality Assurance Data in English (I)VET for the Health Care Sector -- Factors Influencing the Use of Quality Assurance Data in Danish VET for the Health Care Sector -- Factors Influencing the Use of Quality Assurance Data in Estonian (I)VET for the Health Care Sector -- Factors Influencing the Use of Quality Assurance Data in Italian (I)VET for the Health Care Sector -- Factors Influencing the Use of Quality Assurance Data in German (I)VET for the Health Care Sector -- The Factors that Matter for Quality Assurance Across Six Countries -- Guidelines for the Quality Assurance of Vocational Education and Training in EU Countries.
Keywords: Education; Assessment; Education; Assessment, Testing and Evaluation; Professional & Vocational Education; Electronic books